Pliny and the eruption of Vesuvius - Foss, Pedar William (London : Routledge, Taylor & Francis Group, 2022)
Pliny and the Eruption of Vesuvius is a forensic examination of two of the most famous letters from the ancient Mediterranean world: Pliny the Younger's Epistulae 6.16 and 6.20, which offer a contemporary account of the eruption of Vesuvius in AD 79. These letters, sent to the historian Tacitus, provide accounts by Pliny the Younger about what happened when Mt Vesuvius exploded, destroying the surrounding towns and countryside, including Pompeii and Herculaneum, and killing his uncle, Pliny the Elder. This volume provides the first comprehensive full-length treatment of these documents, contextualized by evidence-rich biographies for both Plinys, and a synthesis of the latest archaeological and volcanological research which answers questions about the eruption date. A new collation of sources results in a detailed manuscript tradition and an authoritative Latin text, while commentaries on each letter offer copiously referenced insights on their structure, style, and meaning.Pliny and the Eruption of Vesuvius offers a thorough companion to these letters, and to the eruption, which will be of interest not only to those working on Vesuvius, Pompeii, and Herculaneum, and the works of Pliny but also to general readers, Latin students, and scholars of the Roman world more broadly.
Prologue: Lightning, water, and fire -- 1, Two Plinys -- 2, Two letters -- 3, Two days -- 4, Epistulae 6.16, The Elder's story -- 5, Epistulae 6.20, The Younger's story -- Epilogue
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: Plinius, -- Mladší, -- asi 61-asi 112; 79; 1. století; korespondence -- starověký Řím -- 1. století; literárněvědné rozbory; sopečné erupce -- Itálie -- 1. století; correspondence -- ancient Rome -- 1st century; literary criticism and history; volcanic eruptions -- Italy -- 1st century; Vesuv (Itálie : hora); Vesuvius Mount (Italy); e-knihy online; monografie; e-books online; monographs